2013
DOI: 10.1155/2013/917506
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Asian Snakehead Murrel Channa striata (Channidae) in Malaysia: An Insight into Molecular Data and Morphological Approach

Abstract: Conservation is imperative for the Asian snakeheads Channa striata, as the species has been overfished due to its high market demand. Using maternal markers (mitochondrial cytochrome c oxidase subunit 1 gene (COI)), we discovered that evolutionary forces that drove population divergence did not show any match between the genetic and morphological divergence pattern. However, there is evidence of incomplete divergence patterns between the Borneo population and the populations from Peninsular Malaysia. This supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 41 publications
(60 reference statements)
3
24
1
4
Order By: Relevance
“…The largest ever recorded snakehead was almost six feet long. C. limbata is the smallest species in the Channidae family and ranges from the south of China to Myanmar, Thailand, Laos, Malaysia and Indonesia (Amilhat & Lorenzen 2005;Song et al 2013;Ward-Campbell & Beamish 2005;Wijeyaratne 1994). Adult C. limbata are only 15 to 20 cm in length.…”
Section: Results and Discussion Taxonomic Characteristics Of Channa Lmentioning
confidence: 99%
“…The largest ever recorded snakehead was almost six feet long. C. limbata is the smallest species in the Channidae family and ranges from the south of China to Myanmar, Thailand, Laos, Malaysia and Indonesia (Amilhat & Lorenzen 2005;Song et al 2013;Ward-Campbell & Beamish 2005;Wijeyaratne 1994). Adult C. limbata are only 15 to 20 cm in length.…”
Section: Results and Discussion Taxonomic Characteristics Of Channa Lmentioning
confidence: 99%
“…Colonization of C. striata in Borneo has been consistently postulated to have occurred recently during the Pleistocene glacial maxima when sea levels retreated and the island became interconnected with Java, Sumatra, and the Malay Peninsula, forming the emerged Sunda plains (Molengraaff & Weber, 1919;Woodruff, 2010). Support for the hypothesised ancient river connectivity came largely from the discovery of common mtDNA haplotypes between C. striata in the Malay Peninsula, Sumatra and west Borneo (Song et al, 2013;Tan et al, 2012Tan et al, , 2015, which had been similarly observed in the catfish, Hemibagrus nemurus (Dodson, Colombani, & Ng, 1995).…”
Section: Phylogeography and Genetic Structuring Of C Striata In Sabahmentioning
confidence: 99%
“…Both factors may explain the observed polyphyly (sensu Funk & Omland, 2003) among the geographically isolated groups. For C. striata, mtDNA markers had been demonstrated to be informative for higher level phylogenies (Adamson et al, 2010;Lakra et al, 2010;Song, Munian, Rashid, & Bhassu, 2013;Zhu et al, 2013), but a multi-locus approach is necessary for intra-population studies. In this regard, neutral microsatellite markers are better suited for population-level analyses of C. striata as they are more polymorphic due to absence of selective constraints and because they are usually comprised of randomly segregated, non-linked nuclear DNA loci.…”
Section: Introductionmentioning
confidence: 99%
“…Snakehead (Channa striata Blkr) of family Channidae, is considered as valuable food fish not only in Indonesia (Widodo et al, 2013;Irhamsyah et al, 2017), but also other countries such as Thailand (Khomsab and Wannasri, 2017), Philippines (Jumawan and Seronay, 2017), Vietnam (Quyen et al, 2016), Malaysia (Song et al, 2013), Cambodia (Sinh, 2014), Sri Lanka (Wijeyaratne, 1994), Nigeria (Ama-Abasi and Ogar, 2013), Bangladesh (Islam et al, 2013), India (Kashyap et al, 2014), Pakistan (Najero et al, 2015) and China (Guet al, 2015) due to delicious, high-quality meat fish and availability throughout the year. Snakehead can be commercially cultured in fish farming, earthen ponds, or hapa system (Kumar et al, 2011;Quyen et al, 2016), and culture strategies of them are currently being developed (Xie et al, 2002;Xie et al, 2017;He et al, 2015;Istiyanto and Diana, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They are carnivorous feeders that consume plankton, aquatic insect, mollusks, fish or frogs. Snakeheads from river or swamps are caught by using hooks, gillnet, castnet or fish pot (Song et al, 2013;Irhamsyah et al, 2017). Overfishing, pollution, habitat disruption, disease, and growing human intervention on wetlands is very likely threat to this species (Balkhis et al, 2011;Uthayakumar et al, 2014;Rao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%